DOCOSAHEXAENOIC ACID REVERSES ALUMINIUM INDUCED ALTERATION IN VITAMINS AND LIPID PROFILES IN RAT SERUM - DEVESH KUMAR JOSHI; MANISHA CHOUDHARY; SANDEEP TRIPATHI; AMIT PAL; ABBAS ALI MAHDI (International Journal of Pharma and Bio Sciences, 2013)
Aluminium (Al) is the third most widespread metal in the environment. It is known to be toxic for human and animals. We have studied the effect of simultaneous oral treatment of docosahexaenoic acid on aluminum induced changes in serum lipid profile and vitamins. A total of twenty four male albino rats were taken and divided in to four groups (N=6). First control group was treated with normal saline, second was treated with 100mg DHA, third was treated with 100mg AlCl3 and fourth group was treated with both AlCl3 and DHA. Aluminum treated rats showed a significant increase in serum low density lipoprotein (LDL), very low density lipoprotein (VLDL), triglyceride (TG), Cholesterol (TC) and lipid peroxide level (LPx) while decreased concentration of high density lipoprotein (HDL) and vitamins (A,C and E). DHA administration with Al showed reversal changes near to control in serum lipoprotein ie., LDL, VLDL, HDL, vitamins (A, C and E) and TG level. Moreover, DHA reduces the rate of lipid peroxidation. The results indicate that DHA has some beneficial effect in preventing Al induced toxicity.